2008
DOI: 10.1029/2007gl032622
|View full text |Cite
|
Sign up to set email alerts
|

Probable mixing state of aerosols in the Indo‐Gangetic Basin, northern India

Abstract: [1] To investigate the probable mixing state of aerosols in the Indo-Gangetic Basin, six different mixing cases, viz. external mixing, internal mixing, and four combinations of core-shell type mixing (black carbon, BC over dust, watersoluble over dust, BC over water-soluble and water-soluble over BC) have been considered. Composite single scattering albedo (SSA) have been computed for six cases for postmonsoon, winter and pre-monsoon seasons and are compared with the Aerosol Robotic Network (AERONET) retrieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 20 publications
2
42
0
Order By: Relevance
“…Present study, for the first time, is focused on the monthly variation of clear sky direct aerosol radiation forcing (DARF) over a north Indian station, Delhi, for the whole year during January 2006 to January 2007. Being a part of the Indo-Gangetic Basin the aerosol optical properties over Delhi may resemble what it has been reported earlier from the Indo-Gangetic basin (Dey et al, 2008). It is expected that the anthropogenic aerosols rich in its black carbon (BC) content, present in the atmosphere throughout the year, gets mixed with the mineral dust aerosols from deserts during premonsoon months, April-June.…”
Section: Introductionmentioning
confidence: 59%
“…Present study, for the first time, is focused on the monthly variation of clear sky direct aerosol radiation forcing (DARF) over a north Indian station, Delhi, for the whole year during January 2006 to January 2007. Being a part of the Indo-Gangetic Basin the aerosol optical properties over Delhi may resemble what it has been reported earlier from the Indo-Gangetic basin (Dey et al, 2008). It is expected that the anthropogenic aerosols rich in its black carbon (BC) content, present in the atmosphere throughout the year, gets mixed with the mineral dust aerosols from deserts during premonsoon months, April-June.…”
Section: Introductionmentioning
confidence: 59%
“…Measurement of polydisperse CCN concentrations and submicron aerosol size distributions and total particle (i.e., condensation nuclei, CN) concentrations were made from 26 January- (Dey et al 2008). In terms of weather and seasonal variability, Kanpur experiences four seasons: winter (December-February), premonsoon (March-May), monsoon (June-August), and postmonsoon (September-November) Tripathi et al 2005).…”
Section: Measurement Sitementioning
confidence: 99%
“…They found that LAC was externally mixed in the urban area. Dey et al (2008) did a similar optical closure study in India to infer the mixing states and made an improvement by assuming six cases of aerosol mixing state in the calculation. They found that the probable aerosol mixing state had seasonal variations.…”
Section: Introductionmentioning
confidence: 99%